2012
DOI: 10.1038/ajh.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Prorenin and Renin in Blacks and Whites: Their Relative Abundance and Associations With Plasma Aldosterone Concentration

Abstract: Renin occupies a pivotal position in the generation of angiotensin II and production of aldosterone. Although all renin is derived from prorenin, the prorenin-to-renin ratio tends to differ among individuals with various clinical conditions. 1,2 Elevated levels of prorenin relative to renin can be found, for example, in diabetics with microvascular disease. 3-5 A (pro)renin receptor allows prorenin to display full enzymatic activity. 6 Transgenic rats overexpressing the (pro)renin receptor have elevated aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(20 reference statements)
0
14
2
Order By: Relevance
“…Patients with high plasma renin activity (PRA) respond well to RAAS blockers, some of which suppress renin release 5962 . For example, patients with elevated renin had a greater BP-lowering response to atenolol, an agent that suppresses renin release, than a diuretic 60, 61 .…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with high plasma renin activity (PRA) respond well to RAAS blockers, some of which suppress renin release 5962 . For example, patients with elevated renin had a greater BP-lowering response to atenolol, an agent that suppresses renin release, than a diuretic 60, 61 .…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 99%
“…However, all of those factors are likely interrelated. For instance, AAs have lower renin activity than do whites and have been shown to respond better to atenolol 62, 86 . Patients on a low-salt diet have higher renin activity 57 .…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 99%
“…Retrospective analyses of BP trials confirmed this concept. 61,62 In addition, Gupta et al observed that African Americans, who on average have lower renin levels compared with Caucasians, 63 responded less well to atenolol. 64 Yet, others observed either no role for baseline renin, 65 or at most a weak trend.…”
Section: Determinants Of Raas Blocker Response and The Degree Of Blocmentioning
confidence: 99%
“…In our total HyperPATH cohort study, we confirmed that ALDO, PRA, and potassium levels on a LIB salt diet were lower in AD than ED, as has been shown by others (1)(2)(3)(4)(5)(6)24). Because of limited genotyping data, we also performed analyses in a 2:1 restricted subcohort.…”
Section: Discussionmentioning
confidence: 55%
“…Compared with persons of European descent (ED), individuals of African descent (AD) are known to: (i) be more susceptible to cardiovascular disease (CVD); (ii) have a greater frequency of hypertension (HTN) (particularly salt-sensitive HTN); (iii) have more cardiovascular (CV) damage with HTN; (iv) have lower plasma renin activity (PRA); and (v) more resistant HTN (1)(2)(3)(4)(5)(6). Of interest, these same characteristics also are associated with increased aldosterone (ALDO) production, e.g., primary aldosteronism.…”
Section: Introductionmentioning
confidence: 99%